Hubungan Parenting Self Efficacy dengan Perilaku Agresif Anak Usia Prasekolah di TK ABA 14 Kandangsemangkon Kecamtan Paciran Kabupaten Lamongan: Hubungan Parenting Self Efficacy dengan Perilaku Agresif Anak Usia Prasekolah di TK ABA 14 Kandangsemangkon Kecamtan Paciran Kabupaten Lamongan - Xitri, Windy Rahayu; Maghfuroh, Lilis; Martini, Diah Eko; Rohman, Khoirul; Putri, Meirizky Ella (Jurnal Kesehatan Manarang, 2024)
In preschool years, the ability to socialize, prepare for school, and expand friendships are important factors that can influence a child's behavior. Many behaviors in the child's surrounding environment occur as manifestations of negative behavior in preschoolers because preschoolers are good listeners and imitators. Aggressive behavior refers to individual actions that harm others or damage objects. This study aims to determine the relationship between parenting self-efficacy and aggressive behavior in preschool-aged children at TK ABA 14 Kandangsemangkon, Paciran District, Lamongan Regency. The research design is correlational analytics using a cross-sectional approach. The study population consists of 90 parents, and a sample of 74 parents was obtained using the simple random sampling technique. The data for this study were collected using a questionnaire. After tabulating the data, it was analyzed using the Spearman rho test with p < 0.05. The research results show that the majority of parents with preschool-aged children have low levels of parenting self-efficacy (58.10%), and almost half of the parents have preschool-aged children who have exhibited aggressive behavior (39.19%). Based on the data analysis, the correlation between parenting self-efficacy and aggressive behavior yielded a significant p-value of 0.000 (p < 0.05), and the correlation coefficient value (rs) was found to be 0.505, indicating a strong correlation between parenting self-efficacy and aggressive behavior in preschool-aged children at TK ABA 14 Kandangsemangkon, Paciran District, Lamongan Regency. Based on the research findings, it is expected that parents will enhance their parenting self-efficacy to gain more confidence in their parenting approach, thereby reducing aggressive behavior in preschool-aged children.